Knowledge and Attitudes of Dietitians Concerning Seafood Consumption and Processing/Preservation Technologies - EYGİ ERDOĞAN, BİRSEN (CENTRAL FISHERIES RESEARCH INST, 2015)
This survey was carried out to measure the knowledge and attitudes of dietitians regarding seafood consumption and common processing/preservation technologies. It was also aimed to compare knowledge of dietitians with the other respondents, educated in other sciences. Eighty-five of the respondents were educated in nutrition science (dietitian) and 221 in other sciences (non-dietitian=ND). Opinions of the respondents were generally dependent of being a dietitian (P<0.05). Dietitians were generally against or not recommending the consumption of mussels, lakerda, salted and smoked seafood, while non-dietitians more prone to their consumption. On the other hand, dietitians had a more positive approach to the consumption of canned and frozen seafood, fish oil, surimi, sous-vide and MAP-packed seafood, spirulina, and aquaculture fish than the NDs. It was seen that, most of the processed seafoods are not known by the substantial part of the respondents. Receiving high percentages of the answer I don't know what it is from the dietitians was remarkable, and indicated their ignorance. As a result, the need of dietitian education on seafood products and common processing/preservation technologies was determined. Since dietitians guide consumer preferences, their education may help to achieve a better guided consumer and to improve market recognition of seafood.
Keywords: Survey; consumer preferences; seafood consumption; diet; REGISTERED DIETITIANS; FUNCTIONAL FOODS; FISHERY PRODUCTS; SUPPLEMENTS; SAFETY; RISK